Channel Estimation for the Multiuser Multi-panel Massive Multiple Input Multiple Output System - Ghadiri, Abbas; Atashbar, Mahmoud; Mohassel Feghhi, Mahmood (Wireless personal communications, 2024)
The size and weight of Massive Multiple Input Multiple Output (mMIMO) significantly increase with the addition of more antennas. The 3rd Generation Partnership Project standardization group addressed these issues by incorporating the multi-panel feature into New Radio communications. The estimated value of the channel is essential for signal detection and precoding in mMIMO. Traditional channel estimation methods are ineffective in multi-panel mMIMO system because of its hybrid structure and non-uniform antenna array structure. This paper introduces a novel channel estimation technique for multi-panel mMIMO systems operating in multiuser scenario by transforming the channel estimation problem into an angular domain block sparse signal recovery problem. We propose a generalized block orthogonal matching pursuit (GB-OMP) method to solve the obtained sparse model. The proposed method incorporates a well-designed pilot sequence for optimal performance. The proposed GB-OMP method outperforms the reference method, as shown by the simulation results.